Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/1505394
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Traditional Chinese Medicine on Nonerosive Reflux Disease: A Meta‐Analysis of Randomized Controlled Trials

Abstract: Objectives Traditional Chinese medicine (TCM) therapy for nonerosive reflux disease (NERD) remains controversial. The aim of this study was to evaluate the efficacy and safety of TCM regimens in NERD treatment. Methods Randomized controlled trials (RCTs) of TCM treatment for NERD through September 31, 2017, were systematically identified in PubMed, Wanfang Data, CNKI, VIP, CBM, Ovid, Web of Science, and Cochrane Library databases. Quality assessment was performed by employing the Cochrane Risk of Bias assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…There were 28 reports [ 15 – 24 , 26 – 32 , 34 , 35 , 38 – 45 ] in Chinese and 5 reports [ 25 , 33 , 36 , 37 , 46 ] in English. 18 studies reported the sources of funding; but none of them were Cochrane reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 28 reports [ 15 – 24 , 26 – 32 , 34 , 35 , 38 – 45 ] in Chinese and 5 reports [ 25 , 33 , 36 , 37 , 46 ] in English. 18 studies reported the sources of funding; but none of them were Cochrane reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Methodological quality assessments with the OQAQ and AMSTAR 2 scale suggested that the results of the funding subgroups were similar. According to the PRISMA results, 28 reports [ 15 – 24 , 26 – 32 , 34 , 35 , 38 – 45 ] in Chinese had an average quality score of 19.2, and 5 reports [ 25 , 33 , 36 , 37 , 46 ] in English had an average quality score of 24. The 16 studies [ 17 , 20 , 22 , 24 , 26 – 29 , 31 , 33 , 35 , 37 , 40 – 45 ] that received funding had an average quality score of 19.6, and the nonfunded research had an average quality score of 20.2.…”
Section: Resultsmentioning
confidence: 99%
“…The important role of this membrane-penetrating aquaporin (AQP) is to help water molecules pass through the cell membrane rapidly [10]. It has been proven through experiments [11] that injecting vasoactive intestinal peptide (VIP) into rats with diarrhea increases the VIP expression in serum and intestinal tissues, and the protein expression of AQP is regulated by VIP activity, and the signal pathway of VIP/PKA/AQP in colon epithelial cells is affected, changing the molecular mechanism of intestinal water metabolism and causing the disappearance of diarrheal symptoms [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…As a complementary and alternative medical treatment with fewer adverse effects and certain curative effects, the herbal formulae combined with fixed herbs are widely accepted and studied in China, Japan, South Korea, and other regions. In recent years, through the systematic review of reliable evidence, it has been found that classic TCM herbal formulae, such as Banxia Xiexin Decoction, Wendan Decoction, and others, can effectively improve GERD or some disorders of the gastrointestinal tract (Ling et al, 2015;Teschke et al, 2015;Tominaga and Arakawa, 2015;Dai et al, 2017;Xiao and Yang, 2018). Moreover, our team has collected 122 cases reported in the National Service Platform for Famous and Old Traditional Chinese Medicine (http://www.gjmlzy.com:83) and China National Knowledge Internet (http://www.cnki.net) via data mining based on using effect, flavor, meridian tropism, and syndrome differentiation to cluster analysis of tradition.…”
Section: Introductionmentioning
confidence: 99%